A Note on Performance Evaluation of New Zealand Mutual Funds (International Journal of Banking and Finance, 2006)
This paper reports on the performance of the New Zealand unit trusts over 11 years using the Fama-French three-factor model and the Cahart (1997) unconditional asset pricing test. The results reveal that the funds had negative Jensen’s alphas and thus poor performance. The conditional model shows that funds underperformed the benchmark by 0.34 percent per month. These findings suggest that the funds had poor performance during the tested period. It is puzzling to observe a substantial growth of unit trusts in the same time period despite poor performance of these funds. It is very likely that the fund growth has more to do with regulatory effect of promoting savings than the effect of funds providing above-normal return for the growth of the market.